Phosphate adsorption on goethite and Al-rich goethite - Belelli, Patricia Gabriela (2013)
The adsorption of phosphate complexes on pure and Al-rich goethite surfaces was studied by using density functional theory (DFT) and a periodic slab model. Several phosphate complexes are evaluated on these surfaces, which were not studied in other earlier theoretical works. The following complexes have been considered: bidentate binuclear (BB), bidentate mononuclear (BM), monodentate mononuclear (MM) and monodentate binuclear (MB), with their respective mono-protonated and non-protonated species. Our calculations indicate that the formation of all these species is possible on both goethite surfaces. Particularly, the direct correlation between calculated vibrational frequencies of phosphate complexes on pure goethite and experimental results indicates that some specific species are formed at certain pH values. For these cases we are able to provide an alternative interpretation to the experimental bands. On the other hand, the obtained vibrational frequencies of phosphate adsorbed on Al-goethite can be useful for the forthcoming experimental results. We noticed that the band shifts are extremely dependent on the kind of pretreated samples; for this reason the surface model used in calculations establishes restrictions on the IR experimental results to be compared.